Epidemiology and management of distal radius joint fracture at the Central Military Hospital, between 2000 and 2003 - Garibaldi Tolmos, Paolo A. (2022)
The present is a retrospective transversal work of research that evaluates the treatment of intra-articular distal radius fractures carried out at the Central Military Hospital between the years 2000 y 2003.Out of a total of 586 patients that entered the hospital through the emergency entrance with a diagnosis of distal radio fractures, 196 were selected that presented a total of 203 articular fractures, of which after studying the medical histories and radiographic plates, 148 cases completed the requirements of the chart of recollection of data being this the final population of our study.The greatest incidence is on its majority by mechanisms of high energy was that of the fractures Melone II type (54.1%), followed by those of Melone IV type (22.3%) and the remaining 20% in a varied distribution between those of Melone III and Melone I types. Of the total of cases studied, 77% of the injuries showed ulnar styloid fractures.It was determined that in 54.1% of cases, the open reduction + Kirschner wires was applied as a treatment of fractures Melone II type (53.4%) and Melone I type (0.7%), followed in a 25.0% by those in which was applied the open reduction + plate/screw for fractures Melone III type (14,2%) and Melone IV type (10.8%). The other techniques used, like open reduction + external fixation (Neutralization), closed reduction + percutaneous Kirschner wires and open reduction + external fixation (Ligamentotaxis) were used in a 8.1%, with a 6.1% for Melone IV type and 2.0% for Melone type III; in a 6.8% with 6.1% for the type Melone III type and 0.7% for the Melone II type, and in 6.1% for Melone IV type (5.4%) and the Melone III type (0.7%) respectively.In relation to the use of bone grafting, it took place in a 20% of cases, being the TAC the auxiliary exam in a 75.7% of cases.As a conclusion it is established that in general all the techniques shows high percentages of results rated as excellent or good in the immediate evaluation made after the surgery, being he open reduction + external fixation (ligamentotaxis), the closed reduction + plate/screw and the closed reduction + percutaneous Kirschner wires, the three techniques used with best result, with a 100% in the rangeof these, the open reduction + external fixation (Ligamentotaxis) and the closed reduction + percutaneous Kirschner wires are those which maintain the least variation of results in a late evaluation. The cases in which were used bone grafting are the most stable, showing also that the ulnar styloid fracture would not be in itself a factor of risk for the favorable evolution of these types of injuries.